Modal testing circuit board assembly of an electronic apparatus by laser vibrometry; IOP Conference Series: Materials Science and Engineering; Vol. 156 : Materials and Technologies of New Generations in Modern Materials Science - Krasnoveikin V. A.; Smolin I. Yu. Igor Yurievich; Druzhinin N. V.; Kolubaev E. A.; Derusova D. A. Dariya Aleksandrovna (2016, 2016)
Title screen